2013
DOI: 10.2310/8000.2013.130798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin-resistant Staphylococcus aureus in skin and soft tissue infections in patients presenting to Canadian emergency departments

Abstract: Background:Community-associated methicillin-resistantStaphylococcus aureus(MRSA) is an increasingly common cause of skin and soft tissue infection (SSTI) worldwide. The prevalence of MRSA in SSTIs across Canada has not been well described. Studies in the United States have shown significant geographic variability in the prevalence of MRSA. This study characterizes the geographic prevalence and microbiology of MRSA in patients presenting to Canadian emergency departments with SSTIs.Methods:Using a prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(39 reference statements)
6
20
0
Order By: Relevance
“…In this study, slightly over 30% of the wounds colonized by S. aureus were colonized by MRSA, which is similar to previously reported findings [3,28,30-32]. Even though the present study found a lower rate of wound colonization by S. aureus than in studies conducted in other regions and other countries, the rate of antibiotic resistance was high, which may be attributed to prior antibiotic use by more than a third of the patients, the majority of whom were elderly with comorbidities, and use of multiple antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, slightly over 30% of the wounds colonized by S. aureus were colonized by MRSA, which is similar to previously reported findings [3,28,30-32]. Even though the present study found a lower rate of wound colonization by S. aureus than in studies conducted in other regions and other countries, the rate of antibiotic resistance was high, which may be attributed to prior antibiotic use by more than a third of the patients, the majority of whom were elderly with comorbidities, and use of multiple antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…The present study, which found no HCWs in the sample of 89 ED staff to be colonized with MRSA, and 28.1% MSSA colonization, is the first to document the prevalence of MRSA and MSSA colonization in ED HCWs in Canada. These data are compared with the MRSA and MSSA per cent colonized of 1.9% and 25.9%, respectively, documented in the aforementioned cohort study being conducted in the same ED during the study period (10), and at a time when the prevalence of MRSA in SSTIs at this centre was 30% (15). These population percentages of MRSA colonization are also consistent with recent estimates of MRSA colonization in the general population of the United States (9).…”
Section: Discussionsupporting
confidence: 81%
“…aureus particularly CA-MRSA is the predominant cause of SSTIs worldwide[ 20 ].In our study, 22 isolates (18.8%) of 117 isolates were found as MRSA, and it was lower than the occurrences of MRSA among S . aureus SSTIs previously reported[ 1 , 2 , 21 ].Eight MRSA isolates (3 HA-MRSA and 5 CA-MRSA) were found among non-native patients and 14 MRSA isolates (12 HA-MRSA and 2 CA-MRSA) were found among native patients. We found no significant difference between the occurrences of MRSA in non-native patients compared to native patients.…”
Section: Discussionmentioning
confidence: 99%